A method for continuous rhythm classification and early detection of ventricular fibrillation during CPR. (July 2022) - Kwok, Heemun; Coult, Jason; Blackwood, Jennifer; Sotoodehnia, Nona; Kudenchuk, Peter; Rea, Thomas
Abstract: Aim: We developed a method which continuously classifies the ECG rhythm during CPR in order to guide clinical care. Methods: We conducted a retrospective study of 432 patients treated following out-of-hospital cardiac arrest. Continuous ECG sequences from two-minute CPR cycles were extracted from defibrillator recordings and further divided into five-second clips. We developed an algorithm using wavelet analysis, hidden semi-Markov modeling, and random forest classification. The algorithm classifies individual clips as asystole, organized rhythm, ventricular fibrillation, or Inconclusive while integrating information from previous clips. Classifications were compared to manual annotations to estimate accuracy in an independent validation dataset. Continuous sequences were classified as shockable, non-shockable, or Inconclusive ; classifications were used to compute shock sensitivity and specificity. Results: Of 432 patient-cases, 290 were used for development and 142 for validation. In the 12, 294 validation ECG clips during CPR, accuracies were 0.88 (95% CI 0.85–0.91) for asystole, 0.98 (95% CI 0.98–0.99) for organized rhythm, and 0.97 (95% CI 0.96–0.97) for ventricular fibrillation, with 43% classified as Inconclusive . Of 457 continuous sequences, shock sensitivity was 0.90 (95% CI 0.86–0.93), shock specificity was 0.98 (95% CI 0.93–0.99), and 7% were Inconclusive . Median delay to ventricular fibrillation recognition was 10 (IQR 5–32) seconds. Conclusion: A novel algorithm continuously classified the primary resuscitation rhythms—asystole, organized rhythms, and ventricular fibrillation—with 88–98% accuracy, enabling accurate shock advisory guidance during most two-minute CPR cycles. Additional investigation is required to understand how algorithm implementation could affect rescuer actions and clinical outcomes.